Descriptive epidemiology of soccer injury during elite international competition in africa - Nuhu, A.; Kutz, M. (International Journal of Athletic Therapy & Training, 2017)
Epidemiological research on soccer injuries during African soccer competition is sparse. This study was conducted among 12 teams in the Council of East and Central Africa Football Association (CECAFA) challenge cup tournament. Fifty-seven injuries were reported (2.7 injuries per match), or 82.25 injuries per 1,000 match hours. The ankle was most often injured (23%). The majority (81%) of injuries occurred as a result of traumatic contact, with the most injuries occurring in the last 30 min of the match. A majority (84%) of athletes who sustained injuries continued to play. African medical personnel should be trained to handle the unique constraints and variety of injuries sustained during soccer competition.